The interfacing structural effect of Ag/graphene oxide nanohybrid films on surface enhanced Raman scattering - Kim, Young-Kwan; Ok, Gyeongsik; Choi, Sung-Wook; Jang, Hongje; Min, Dal-Hee (ROYAL SOC CHEMISTRY, 2017)
The interfacing structural effect of Ag/graphene oxide (GO) nanohybrid films on SERS was investigated by using Ag nanostructures immobilized on polyallylamine hydrochloride (PAA) functionalized-GO and reduced GO (RGO) films. We found that the electron transfer from Ag nanostructures to GO derivatives dominantly occurred at the interfaces between Ag nanostructures and the sp(2) carbon domains of GO and RGO films. By utilizing 4-aminothiophenol (4-ATP) as a Raman probe, it was revealed that this electron transfer process augmented the enhancement factor (EF) of 4-ATP up to similar to 1.8 fold on Ag/PAA-RGO nanohybrid films compared to Ag/PAA-GO nanohybrid films with the increasing interfacing area between Ag nanostructures and the sp(2) carbon domains of GO derivatives through wet-chemical processes.
Keywords: REDUCED GRAPHENE OXIDE; PLASMON RESONANCE; METAL NANOPARTICLES; GOLD NANOSTRUCTURES; LARGE-SCALE; SILVER; PLATFORM; AMINOTHIOPHENOL; SUBSTRATE; GROWTH